Musculoskeletal pain among bakery workers in Lebanon: a national survey. Issue 1 (1st January 2019) - Habib, Rima R.; El-Harakeh, Amena; Hojeij, Safa
Abstract: This study examined the association of self-reports of repetitive hand movements, perceptions of the work environment, and somatization with upper extremity musculoskeletal pain among bakery workers, an understudied population globally. Surveys were conducted in 504 randomly selected bakeries across Lebanon and administered through face-to-face interviews at the workplace. The survey included items on musculoskeletal pain, general health, workplace environment, activities, and socio-demographics. The findings showed that 23% of bakery workers reported upper extremity pain. Workers who reported poor health (OR = 2.08; 95% CI = 1.12–3.87) and those who perceived that the work environment negatively affects their health (OR = 2.04; 95% CI = 1.26–3.33) were twice as likely to experience upper extremity musculoskeletal pain. Somatization was positively associated with reporting upper extremity musculoskeletal pain (OR = 1.51; 95% CI = 1.22–1.86). Workers that reported having another job were three times more likely to report upper musculoskeletal pain (OR = 2.76; 95% CI = 1.31–5.79). The need for interventions in the work environment and work strategies is evident.